Karakteristik Penggusuran di Indonesia: Pentingnya Intervensi HAM Sebelum, Sewaktu, dan Setelah Penggusuran - Mochamad Felani Budi Hartanto; Dian Andi Nur Aziz; Agus Suntoro (Badan Strategi Kebijakan Hukum, 2023)
Development and spatial planning policies, especially physical infrastructure, are closely tied to the changes in land use. When these policies intersect with public living spaces, there is a possibility that they are leading to eviction. Although driven by public interest considerations